The Occupier’s Civil Liability in the English Law. An Analytical Comparative Study with the Iraqi Civil Law - علي يونس صلاح الدين (Journal of Legal Sciences, 2020)
The occupier’s civil liability in English law is considered as one of the main types of the responsibility imposed by the law of Torts. and is regarded as a special system of the civil liability arising from negligence, as well as two other systems, that is to say , the employer’s non-contractual liability and The liability from defective products. It is worth-bearing in mind that the common law has imposed on the occupier of the premises a duty of safety towards those who enter his premises. And two English legislations have been enacted later to regulate this type of liability legislatively, namely, the Occupier’s liability Act 1957 and the Occupier’s liability Act 1984. Whereas the Iraqi civil law No. 40 of 1951 has regulated the liability for the building, which takes two forms: the liability arising from the collapse of the building or it’s falling, and the liability resulting from what is thrown from or falling from the residence.